The detection of plasmid transfer genes in Rhizobium species : a thesis presented in partial fulfilment of the requirement for the degree Master of Science in Microbiology at Massey University, New Zealand - Fisher, Paul Jamie (Massey University, 1994)
In order that Rhizobium tra genes responsible for Sym plasmid transfer might be found, DNA probes were constructed from Agrobacterium tra genes. Three probes were constructed from DNA containing;- 1) traR, a gene which regulates other tra genes on the Agrobacterium tumefaciens plasmid pTiC58, 2) an OriT site, at which nickases cleave the plasmid before conjugal transfer can take place, and 3) part of a gene required for construction of a mating bridge. All three probes were constructed by the ligation of tra areas from the A.tumefaciens strain C58 plasmid pTiC58 into broad host range plasmid vectors and subsequent electroporation into E.coli cells. The genomic DNA digests of several Rhizobium and Agrobacterium strains were blotted and probed with the three probes under various washing and hybridisation stringencies. A.tumef aciens strain LMG64 was the only Agrobacterium strain aside from strain C58 to have DNA homologous to any of the probes. Neither R.leguminosarum bv trifolii strain ICMP2163, nor R. leguminosarum bv trifolii strain ICMP2163::Tn5, nor R.leguminosarum bv trifolii strain PN165 had any DNA homologous to any of the probes. However, R.leguminosarum bv trifolii strain ATCC14480 showed homology to the tra I probe (containing traR), and R.loti strain ATCC33669, phylogenetically the most distant relative to A.tumefaciens strain C58 shared homology with the tra III probe (containing DNA responsible for mating bridge assembly). Therefore the distribution of tra genes from the Ti plasmid of A.tumefaciens strain C58 among the agrobacteria and rhizobia used in this study did not correlate to their phylogenetic relatedness to A.tumefaciens strain C58 or to one another.
Keywords: Nitrogen fixing microorganisms; Genetics; Plant molecular genetics; Rhizobium